Preoperative Frailty and Postoperative Adverse Outcomes among Elderly Patients with Gastric Cancer - MIAO Xueyi, DING Lingyu, LU Jinling, HU Jieman, ZHU Hanfei, CHEN Li, XU Xinyi, XU Qin (Zhongguo quanke yixue, 2023)
Background Due to great differences in physiological reserve, psychological status and social functioning, frailty in elderly patients with gastric cancer may present various subtypes. The relationship between preoperative frailty and postoperative adverse outcomes in them still remains to be further explored. Objective To explore the relationship between preoperative frailty subtypes and postoperative adverse outcomes〔total complications, prolonged length of stay (PLOS), low quality of life (QOL), and disability〕among elderly patients with gastric cancer. Methods From March to October 2021, 404 elderly gastric cancer patients were selected from Department of Gastric Surgery, the First Affiliated Hospital with Nanjing Medical University by convenience sampling. The General Demographic Data Questionnaire and Tilburg Frailty Indicator were used to collect demographics and frailty status before surgery. Total complications and PLOS were collected from the electronic medical records, and the status of disability and QOL were obtained using a telephone follow-up at one month after discharge. Univariate Logistic regression was performed to explore the influencing factors of postoperative adverse outcomes. Multivariate Logistic regression analysis was performed to analyze the association of preoperative frailty subtypes with postoperative adverse outcomes, with potential confounders adjusted. Results Two hundred and eighty-five cases were found with preoperative frailty, and the frailty subtypes in them were classified into eight classes: exclusive physical frailty〔77 (19.1%) 〕, exclusive psychological frailty〔78 (19.3%) 〕, exclusive social frailty〔23 (5.7%) 〕, physical and psychological frailty〔63 (15.6%) 〕, physical and social frailty〔13 (3.2%) 〕, psychological and social frailty〔16 (4.0%) 〕, multidimensional frailty (physical, psychological, and social frailty) 〔15 (3.7%) 〕. The other 119 (29.5%) cases had no preoperative frailty. In the univariate Logistic regression, age was the factor influencing total complications〔OR=1.063, 95%CI (1.021, 1.106), P=0.003〕. History of pharmacological treatment〔OR=1.549, 95%CI (1.016, 2.362), P=0.042〕and surgical approach〔OR=2.103, 95%CI (1.191, 3.712), P=0.010〕were the factors influencing PLOS. Marital status〔OR=4.611, 95%CI (1.079, 19.706), P=0.039〕, living in an urban area〔OR=1.614, 95%CI (1.009, 2.582), P=0.046〕, having at least two comorbidities〔OR=1.694, 95%CI (1.038, 2.766), P=0.035〕were the factors influencing postoperative low QOL. Living in an urban area〔OR=0.601, 95%CI (0.390, 0.926), P=0.021〕, history of pharmacological treatment〔OR=1.663, 95%CI (1.082, 2.558), P=0.020〕, and advanced TNM stages〔OR=1.659, 95%CI (1.017, 2.706), P=0.043〕were the factors influencing postoperative disability. In the multivariate Logistic regression, the preoperative multidimensional frailty was independently associated with total complications, with age adjusted〔OR=5.344, 95%CI (1.715, 16.656), P=0.004〕. The preoperative physical frailty〔OR=2.048, 95%CI (1.078, 3.891), P=0.029〕, preoperative psychological frailty〔OR=2.077, 95%CI (1.103, 3.913), P=0.024〕and preoperative multidimensional frailty〔OR=8.321, 95%CI (2.400, 28.848), P<0.001〕were independently associated with PLOS, with history of pharmacological treatment and surgical approach adjusted. Preoperative psychological frailty〔OR=2.620, 95%CI (1.267, 5.418), P=0.009〕, preoperative psychological and social frailty〔OR=11.122, 95%CI (3.253, 38.028), P<0.001〕and preoperative multidimensional frailty〔OR=11.579, 95%CI (2.835, 47.302), P<0.001〕were independently associated with postoperative low QOL, with marital status, living in an urban area, and having at least two comorbidities adjusted. Conclusion Medical professionals should pay attention to preoperative frailty prevalence in elderly gastric cancer patients, and assess preoperative frailty in these patients using tools with the multidimensional frailty scale included, and attach great importance to those with exclusive physical frailty, exclusive psychological frailty, psychological and social frailty, and multidimensional frailty before surgery. A targeted prerehabilitation intervention program can be delivered to those with preoperative frailty according to their subtypes of frailty to improve postoperative adverse outcomes and QOL.